Menyalakan Kembali Pelita Injil Yesus Kristus Di Era Pasca-Kebenaran Berdasarkan Matius 5:14-16 - Tatanegara, Kondang Sri; suhadi, suhadi; Sukarno, Mahattama Banteng (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2024)
Abstract: Misinformation and "false" truths have threatened the harmony of religious and cultural communities. In the context of Christianity, they are also a threat to the building of the faith of the disciples of Jesus Christ, both cognitively, affectively, and psychometrically. The researcher sees the need to rekindle the lamp of the Gospel of Jesus Christ through two research questions, among others: first, why is it important to "rekindle the lamp of the Gospel of Jesus Christ in the post-truth era," and second, how to "rekindle the lamp of the Gospel of Jesus Christ in the post-truth era." Using Norman Fairclough's Critical Discourse Analysis paradigm on Matthew 5:14-16 in dialogue with a postcolonial perspective, the researcher sees that re-lighting the Gospel of Jesus Christ is important. In addition, this research concludes with an alternative conceptual practical guideline on how to rekindle the Gospel of Jesus Christ. Abstrak: Misinformasi dan kebenaran "palsu" telah menjadi ancaman bagi keharmonisan dalam masyarakat agama dan budaya. Dalam konteks kekristenan, kedua hal tersebut juga menjadi ancaman dalam membangun iman para murid Yesus Kristus, baik secara kognitif, afektif, pun psikomotorik. Melalui dua pertanyaan penelitian, antara lain: pertama, mengapa "Menyalakan Kembali Pelita Injil Yesus Kristus di Era Pasca-Kebenaran" adalah penting dilakukan pada masa kini? dan kedua, bagaimana "Menyalakan Kembali Pelita Injil Yesus Kristus Di Era Pasca-Kebenaran?" peneliti memandang perlu menyalakan kembali pelita Injil Yesus Kristus. Dengan mempergunakan paradigma Analisis Wacana Kritis dari Norman Fairclough terhadap Matius 5:14-16 yang dialogkan dengan perspektif pasca kolonial, peneliti melihat bahwa tindakan menalakan pelita kembali Injil Yesus Kristus adalah penting dilakukan. Selain itu, penelitian ini diakhiri dengan alternatif pedoman praktis secara konseptual bagaimana meyalakan pelita kembali Injil Yesus Kristus.